Codes for entanglement-assisted classical communication - Tushita Prasad; Markus Grassl (npj Quantum Information)
Abstract Entanglement-assisted classical communication (EACC) aims to enhance communication systems using entanglement as an additional resource. However, there is a scarcity of explicit protocols designed for finite transmission scenarios, which presents a challenge for real-world implementation. In response, we introduce a new EACC scheme capable of correcting a fixed number of erasures/errors. It can be adjusted to the available amount of entanglement and sends classical information over a quantum channel. We establish a general framework to accomplish such a task by reducing it to a classical problem. Comparing with specific bounds, we identify optimal parameter ranges. The scheme requires only the implementation of super-dense coding which has been demonstrated successfully in experiments. Furthermore, our results show that an adaptable entanglement use confers a communication advantage. Overall, our work sheds light on how entanglement can elevate various finite-length communication protocols, opening new avenues for exploration in the field.